Co-adaptation processes in plenary teacher-student talk and the development of L2 interactional competence. Issue 3 (2nd July 2020) - Konzett-Firth, Carmen
ABSTRACT: This paper shows how a language teacher and her students observably recalibrate their interactional behaviour over time. With respect to the students, this recalibration can be interpreted as increased L2 interactional competence. The participants' turn designs indicate that they are contingent upon: 1) the local interactional context; 2) the students' changing linguistic and interactional competence; and 3) the teacher's evolving pedagogical goals. The phenomenon is examined in oral collective reconstructions of reading texts in plenary teacher-student talk. The data stems from a longitudinal corpus of video-recorded classroom interaction, distributed over 5 schoolyears of instructed L3 French. The analysis focuses on the way the teacher's questions, the students' responses and the teacher's subsequent third turns are formatted with regard to the use of linguistic resources afforded by the reading texts. At the pre-intermediate level, the teacher invites and reinforces the use of afforded linguistic elements, while the students' answer turns are characterized by appropriations of linguistic resources from the teacher's talk or the reading text. Towards the intermediate level, the teacher's turns increasingly reflect a changing pedagogical agenda allowing for more learner agency, while the students' turns exhibit a more fine-tuned recipient design despite fewer afforded elements.